Multifactorial Model to Predict Response to PD-(L)1 Blockade in Patients with High PD-L1 Metastatic Non-Small Cell Lung Cancer - Arbour, K.; Oprescu, Miruna; Hakim, J.; Rizvi, H.; Leiserson, M.; Ginsburg, M.; Plodkowski, A.; Sauter, J.; Preeshagul, I.; Gillett, Sharon; Rosenfield, Philip; Mackey, Lester; et al. (Journal of Thoracic Oncology, 2019)
High PD-L1 expression (≥50%) is a routine biomarker but is incompletely predictive, with response rates to PD-1 monotherapy only 35-45% in patients with lung cancer. Beyond PD-L1, additional individual pre-treatment variables, including clinical (smoking history, BMI), genomic (TMB, STK11, EGFR), and laboratory features (baseline dNLR), individually associate with response but have not been comprehensively examined in combination. We hypothesized that a multifactorial model incorporating routinely available clinical, pathologic, and genomic variables could improve prediction of response in high PD-L1 patients receiving first line anti-PD-(L)1 monotherapy.